PENGARUH KEPEMIMPINAN DAN KOMPENSASI TERHADAP KINERJA KARYAWAN PADA PT. DHARMA INTI TEKNOLOGI - Muh Chairul Anshar; Surya Kelana Basri; Dahlan Dahlan (Movere Journal, 2023)
This study aims to determine the effect of leadership and compensation on employee performance at PT. Dharma Inti Technology. The types of data used in this study are qualitative data and quantitative data. Sources of data used are primary data and secondary data. Data analysis method used is multiple regression analysis, correlation coefficient, coefficient of determination, f-test and t-test. Regression results state that leadership and compensation simultaneously have a positive and significant effect on employee performance. Leadership partially has a positive and significant effect on employee performance. Partial compensation has a positive and significant effect on employee performance.